Art Hamburg : Kunst kennt keine Grenzen. - Art Hamburg, 1990 (Hamburg : Hamburg Messe und Congress GmbH, 1990)
Postma, Gerriet ; Vandaele, Jean-Noël ; Van der Laan, Wil ; Kranemann, Eberhard ; Fonseca, Harry ; Young, Yamin ; Kortekaas, Pieter ; Cecioni, Marco ; Dolores ; Kirke, Franceska ; Hajek, O.H. ; Panek, Erkehardt ; etc.
Art Hamburg : Kunst kennt keine Grenzen, Internationale kunstmesse, Hamburg, 6. - 11.12.1990
boek